2019
DOI: 10.1016/j.celrep.2019.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in BDNF/TrkB Neurotrophic Activity Stimulates δ-Secretase by Upregulating C/EBPβ in Alzheimer’s Disease

Abstract: SUMMARY BDNF/TrkB neurotrophic signaling regulates neuronal development, differentiation, and survival, and deficient BDNF/TrkB activity underlies neurodegeneration in Alzheimer’s disease (AD). However, exactly how BDNF/TrkB participates in AD pathology remains unclear. Here, we show that deprivation of BDNF/TrkB increases inflammatory cytokines and activates the JAK2/STAT3 pathway, resulting in the upregulation of transcription factor C/EBPβ. This, in turn, results in increased expression of δ-secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 57 publications
(73 reference statements)
4
87
3
1
Order By: Relevance
“…In support, we showed that microglia and astrocyte-induced neuroinflammation plays a crucial role in the development of POCD. Moreover, alteration in BDNF signaling can result in synaptic dysfunction that is associated with memory deficits observed in AD [48], Parkinson's disease (PD) [41], stroke [49], and sepsisassociated encephalopathy [50]. In the present study, we showed that anesthesia and surgery induced decreased levels of BDNF, which could be reversed by memantine and MDL-28170.…”
Section: Discussionmentioning
confidence: 47%
“…In support, we showed that microglia and astrocyte-induced neuroinflammation plays a crucial role in the development of POCD. Moreover, alteration in BDNF signaling can result in synaptic dysfunction that is associated with memory deficits observed in AD [48], Parkinson's disease (PD) [41], stroke [49], and sepsisassociated encephalopathy [50]. In the present study, we showed that anesthesia and surgery induced decreased levels of BDNF, which could be reversed by memantine and MDL-28170.…”
Section: Discussionmentioning
confidence: 47%
“…4 , 5 , and 7 ). Our previous study demonstrated that BDNF and C/EBPβ inversely regulate each other, providing a mechanistic link between BDNF/TrkB reduction, C/EBPβ up-regulation, δ-secretase (AEP) activation, and Aβ and Tau alterations in the murine brains ( 39 ). In the current study, we found that R13 (7,8-DHF) also functions as antioxidant in the murine colon, leading to proinflammatory cytokine IL-6 decrease and suppression of C/EBPβ.…”
Section: Discussionmentioning
confidence: 99%
“…TrkB-expressing neurons in the dorsomedial hypothalamus act as critical regulators of energy expenditure and body weight through appetite suppression and an increase in satiety [9]. Furthermore, the downregulation of TrkB expression is associated with the pathogenesis of Alzheimer's [10,11], Huntington's [12,13], and Parkinson's [14,15] diseases. Conversely, TrkB is aberrantly overexpressed in a variety of human cancers [16][17][18].…”
Section: Introductionmentioning
confidence: 99%